GSK-3β Contributes to Parkinsonian Dopaminergic Neuron Death: Evidence From Conditional Knockout Mice and Tideglusib - Li, Junyu; Ma, Shanshan; Chen, Jingnan; Hu, Kunhua; Li, Yongyi; Zhang, Zeyu; Su, Zixiang; Woodgett, James R.; Li, Mingtao; Huang, Qiaoying (Frontiers in Molecular Neuroscience, 2020)
Glycogen synthase kinase-3 (GSK-3) dysregulation has been implicated in nigral dopaminergic neurodegeneration, one of the main pathological features of Parkinson’s disease (PD). The two isoforms, GSK-3α and GSK-3β, have both been suggested to play a detrimental role in neuronal death. To date, several studies have focused on the role of GSK-3β on PD pathogenesis, while the role of GSK-3α has been largely overlooked. Here, we report in situ observations that both GSK-3α and GSK-3β are dephosphorylated at a negatively acting regulatory serine, indicating kinase activation, selectively in nigral dopaminergic neurons following exposure of mice to 1-methyl-4-pheny-1,2,3,6-tetrahydropyridine (MPTP). To identify whether GSK-3α and GSK-3β display functional redundancy in regulating parkinsonian dopaminergic cell death, we analysed dopaminergic neuron-specific Gsk3a null (Gsk3a△Dat) and Gsk3b null (Gsk3b△Dat) mice, respectively. We found that Gsk3b△Dat, but not Gsk3a△Dat, showed significant resistance to MPTP insult, revealing non-redundancy of GSK-3α and GSK-3β in PD pathogenesis. In addition, we tested the neuroprotective effect of tideglusib, the most clinically advanced inhibitor of GSK-3, in the MPTP model of PD. Administration of higher doses (200 mg/kg and 500 mg/kg) of tideglusib exhibited significant neuroprotection, whereas 50 mg/kg tideglusib failed to prevent dopaminergic neurodegeneration from MPTP toxicity. Administration of 200 mg/kg tideglusib improved motor symptoms of MPTP-treated mice. Together, these data demonstrate GSK-3β and not GSK-3α is critical for parkinsonian neurodegeneration. Our data support the view that GSK-3β acts as a potential therapeutic target in PD and tideglusib would be a candidate drug for PD neuroprotective therapy.